Evaluation of the bond strength of different intraradicular posts in endodontically treated teeth - Dias Caldeira , François Isnaldo (2025)
Objectives: The reconstruction of endodontically treated teeth with significant coronal destruction often requires the use of posts. This study evaluated the bond strength of four intraradicular post systems in different root regions using a push-out test: conventional fiberglass, CAD/CAM fiberglass, Splendor SAP, and anatomical posts. Materials and Methods: Nineteen single-rooted premolars were treated endodontically and divided into four groups. The posts were cemented with dual self-adhesive resin cement and then sectioned into 1 mm slices for push-out testing. Results: The cervical region had a higher bond strength than middle and apical thirds. Conventional fiberglass posts presented higher resistance than anatomical posts (p=0.048). Conclusions: These results confirm that cervical thirds present the best bonding conditions and that conventional fiberglass posts outperform the anatomical ones.